Urban transformation in Algeria’s high plateaus: GIS evidence from Setif (2000–2025) - Arif, Khoula; Kharchi, Tahar (Art Law and Accounting Reporter, 2026)
This article examines the multidimensional urban transformation of Setif over the first quarter of the twenty-first century. Drawing on GIS-based spatial analysis, official statistical data, and an original Triple Integration Model that links demographic, spatial, and economic dynamics, the study traces urban transformations in Setif municipality over the period from 2000 to 2025. The analysis reveals that rapid population growth (from 243,000 in 2000 to 421,500 inhabitants in 2025), combined with large-scale state housing programmes and strategic infrastructure investment, propelled the city into the role of a ’Gateway City’ and regional economic hub for Algeria’s High Plateaus. However, this quantitative leap was achieved at significant cost: 1,790 hectares of productive agricultural land were consumed, morphological incoherence proliferated, and urban governance mechanisms proved unable to keep pace with spatial dynamics. The article argues that Setif embodies a broader paradox common to rapidly urbanising cities in the Global South: functional metropolitan success coexisting with structural spatial imbalance and governance deficits. Policy implications for land-use regulation, investment law, and sustainable urban planning are discussed in the light of national and international frameworks.